PERAN PENDIDIKAN KEWARGANEGRAAN DAN ILMU PENDIDIKAN SOSIAL DALAM MEMBENTUK KARAKTER GENERASI MUDA - Affan, M. Hussin; Maksum, Hafidh (Jurnal Pesona Dasar, 2020)
Citizenship and social education education plays a role in the development and development of character in the younger generation, if the contribution given by citizenship and social studies education is successful in directing the young generation today to contribute to the national character. Therefore, it is very necessary to have an understanding of the character of the nation itself and provide a way for the development of the nation's character. the development of superior national character has existed since the republic was proclaimed on August 17, 1945. Our first national leader, Bung Karno, had stated the need for nation and character buildings. Although the statement is in a political context, it explicitly implies that Indonesia's development is not enough just to develop physically but must include building the character and culture of the nation. Some national figures of this nation such as Ki Hadjar Dewantoro also mentioned the need for character building as an integral part of national development. One effort that can realize these characters is using or injecting an educational institution that is very close to each of the nation's next generation. A media needs to be implemented namely through a course and citizenship education and social studies subjectsÂ